Exploiting earthquake-induced landslide inventories for macroseismic assessment using the environmental seismic intensity (ESI-07) scale - Eliana Muccignato; Maria Francesca Ferrario (Frontiers in Earth Science)
Earthquake-induced landslides are one of the most impacting effects triggered by seismic events and represent a relevant risk factor. Inventories of earthquake-induced landslides are available for many case histories and may contain thousands of elements. The spatial pattern of landslides is typically analyzed in terms of density and areal coverage (LND: Landslide Number Density; LAP: Landslide Area Percentage). In addition to landslides, other earthquake environmental effects, such as surface faulting, liquefaction, or tsunami, may be triggered. A comprehensive evaluation of earthquake environmental damage can be achieved using the Environmental Seismic Intensity (ESI-07) scale; however, landslide inventories have not yet been fully exploited in terms of ESI-07 assessment. Here, we apply a grid-based methodology to compute LND, LAP and ESI-07 values for 40 landslide inventories related to 33 earthquakes worldwide. We derive the first empirical equations relating ESI-07 to LND or LAP, demonstrating that the LAP metric is more robust. We also find that the inventory itself (i.e., how landslide polygons are delineated) introduces much higher uncertainty into the process compared to the selection of a specific area-volume conversion equation. A comparison with independent ESI-07 data shows that the proposed procedure is reliable. We claim that our approach can be applied in other contexts and could represent the basis for enhanced collaboration between the scientific communities working on landslides and seismic intensity assessment.